Re-Engineering Teaching Profession for Sustainable Development in Nigeria: Perspectives of Education Stakeholders - Nzeako, Constance Uzoamaka; Onyekaba, Martha Nnamaka (International Journal of Human Kinetics, Health and Education, 2023)
The issue of re-structuring teaching profession for sustainable development in Nigeria has often been a matter of serious concern to educationists, academics and the government. The study focused on what the stakeholders in education should do to re-engineer teaching profession to achieve sustainable development in Nigeria. It adopted a descriptive survey design. The population of the study comprised 40 respondents which was made up of 20 Senior Officers in the Ministry of Education and 20 Senior Officers in the Teachers’ Registration Council of Nigeria, Awka respectively. Out of this population, a sample of 20 respondents was used for the study. Their views were randomly sampled, using simple random sampling technique. The instrument for data collection was a structured 10- item questionnaire designed by the researchers and validated by experts in the Ministry of Education and Teachers Registration Council of Nigeria (TRCN). A 4 - point rating scale of Strongly Agree (SA), Agree(A), Disagree (D) and Strongly Disagree(SD) was used to measure the responses of the respondents, to ascertain their degree of approval or disapproval to the questionnaire items, which consisted of various statements on the topic under study. The data generated through the questionnaire were analyzed using Mean and Standard Deviation. The findings of the study showed that efforts are now being made to re-position teaching profession in Nigeria. For instance, there is a recent memo from (TRCN) that mandates teachers to write qualifying examination, before being registered as teachers, among others. Based on the findings of the study, the researchers recommended for a robust policy and due recognition of teaching profession in Nigeria.